Alleviation of O2 competition with NO in electrochemical reduction through nanoceria supported on LSM cathode. (1st November 2022) - Zheng, Yuan; Shi, Huangang; Qu, Jifa; Yu, Yang; Wu, Shuaini; Tan, Chong; Tan, Wenyi
Graphical abstract: Highlights: Nano-sized ceria infiltrated on LSM can alleviate negative impact of oxygen on NO electrochemical reduction. Higher OSC of LSM-GDC(nano) and oxygen vacancies regeneration under polarization favors to extend the limit of oxygen tolerance. Besides OSC, gas or chemical diffusion is another key kinetic limit to improve performance. Abstract: Inhibition of O2 competing with NO will promote NO electrochemical abatement, and further will facilitate its application in the purification of exhaust emitted from a gasoline engine. This study discovered that (La0.75 Sr0.25 )0.95 MnO3 cathode with nano-sized Ce0.9 Gd0.1 O1.95 (GDC) particles (denoted as LSM-GDC(nano)) in solid-state cell can alleviate the negative impact of oxygen content on NO conversion. When oxygen content increases gradually from 0 to 1%, NO conversions decrease to 60% and 30% for LSM-GDC(nano) and LSM-GDC cathodes, respectively. In comparison with LSM-GDC, the abundance of oxygen vacancies available for oxygen adsorption in LSM-GDC(nano) is responsible for higher OSC values under polarization. Postmortem XPS spectra of Ce 3d for the cathodes further confirm that Ce 4+ reduction- into Ce 3+ under polarization can regenerate oxygen vacancies, and that the redox cycle of Ce 4+ /Ce 3+ between polarization and external atmosphere takes place during electrochemical reduction of NO. The DRT method precisely reveals that LSM-GDC(nano) improves adsorption and dissociation of O2 significantly, which is also confirmed by DFT calculations. However, the limit of gas/chemical diffusion is still prominent in the presence of relatively higher oxygen content, even at higher applied voltages.